Competência em informação: perspectivas em torno da cultura escolar - Pereira, Rodrigo; Casarin, Helen de Castro Silva [UNESP] (My University, 2012)
Displays the Information Literacy as a method of training for access, evaluation and use of information, which has become, increasingly, the raw material indispensable for intellectual autonomy. Presents the articulation possible - and necessary - between Information and Cultural Competence in School, with emphasis on their relationship. Search is on School Culture, contexts for insertion of procedures developed by the Information Literacy, considering the dimensions of the organization, interpretation and knowledge production. It points out the advantages to realize the Culture School, through practical philosophical context, to support action planning, establishing, in the educational environment, actions related to the development of Competency Information. We used participation research action in the context of a public school in Campo Grande-MS, the research subjects were students of the 6º and 7º grades and their teachers. Data collection took place through observation and interviews relating the development of competencein Information and teaching practices It is noteworthy that this kind of responsibility if developed without an understanding of school culture, becomes a rambling and disjointed practice whose outcomes are at risk of not being achieved.

Apresenta a Competência em Informação como metodologia de formação para o acesso, avaliação e uso da informação, a qual se tem tornado, cada vez mais, insumo indispensável à autonomia intelectual. Apresenta a articulação possível - e necessária - entre Competência em Informação e a Cultura Escolar, dando ênfase às suas relações. Busca-se, na Cultura Escolar, contextos para inserção de procedimentos desenvolvidos por meio da Competência em Informação, considerando as dimensões da organização, interpretação e produção de conhecimento. Aponta as vantagens de se perceber a Cultura Escolar, através do contexto prático filosófico, como suporte ao planejamento de ações que instituam, no ambiente educacional, ações relacionadas ao desenvolvimento da Competência em Informação. Ressalta-se que esse tipo de competência, se desenvolvida sem a compreensão da Cultura Escolar, torna-se uma prática desconexa e desarticulada cujos resultados esperados correm o risco de não serem alcançados.
Information literacy: prospects around the school culture
Keywords: competência em informação; cultura escolar; ensino fundamental